P0485ASSOCIATION BETWEEN ANTI-GBM TITERS AND KIDNEY INFLAMMATION MEASURED BY A NEW ACTIVITY SCORE. (6th June 2020) - Hermida-Lama, Evelyn; Rodríguez, Diana; Cucchiari, David; Blasco, Miquel; Piñeiro, Gaston; Poch, Esteban; Lozano, Miquel; Cid, Joan; Ruiz-Ortiz, Estibaliz; García-Herrera, Adriana; Quintana, Luis F; Molina Andãºjar, Alãcia
Abstract: Background and Aims: Anti-glomerular basement membrane (anti-GBM) disease is an aggressive and rare glomerulopathy characterized by rapidly progressive loss of kidney function, leading to end stage kidney disease (ESKD) in a significant amount of cases. The main objective of our study was to determine whether anti-GBM titer correlated with the rate of activity in renal biopsy and long-term kidney survival in patients with anti-GBM, hence identifying patients who would potentially benefit from more intensive treatments. Method: A retrospective analysis was performed on the cases of anti-GBM from our center that had both a positive biopsy and serology, from 2007 to 2019. Epidemiological data, anti-GBM levels on admission, kidney function at admission, discharge and follow-up, treatment and kidney biopsy findings were collected. All biopsies were reevaluated by a single, blinded pathologist and nephrologist. Based on a recent study by van Daalen et al, a chronicity and activity histopathological score was developed. The score was divided in glomerular and interstitial sections. In the glomerular section, a sclerotic pattern (>50% of glomeruli) was given 0 points in activity and 3 in chronicity, a mixed pattern was given 1 point in activity and chronicity, and a crescentic pattern (>50% with cellular crescents) was given 3 points in activity and 0 in chronicity. In the interstitial section, the presence of fibrosis and atrophy was given between 0 and 3 points in chronicity and the presence of tubulitis or interstitial infiltrate were given points in activity (0 to 1 and 0 to 3 respectively). The presence of neutrophils in the infiltrate was given one extra point in activity. Spearman correlation was performed between anti-GBM levels and our biopsy score. Results: Twelve cases were identified, with a median Anti-GBM titer at admission of 292 U/mL (IQR 40-1517). Ten patients were treated with cyclophosphamide, 1 with rituximab plus cyclophosphamide and 1 with only rituximab. All patients received treatment with metilprednisona and plasma exchange with a median number of sessions of 8 (range: 6-12). Only one patient was not in ESKD during follow-up (35 months), so correlation with long-term kidney survival could not be performed. On the other hand, high antibody titers correlated with more activity on biopsy (correlation coefficient 0.592, p= 0.042) and less chronicity (correlation coefficient -0.657, p= 0.02). Conclusion: These results suggest that patients who present with higher titers have more acute inflammation and less chronicity in renal parenchima, and therefore could benefit from more intensive treatment that changes the natural history of this aggressive disease. It would be interesting to study this score in larger and multicentric cohorts in order to produce more definitive conclusions.